2013
DOI: 10.1016/j.carbon.2013.04.074
|View full text |Cite
|
Sign up to set email alerts
|

A tough graphene nanosheet/hydroxyapatite composite with improved in vitro biocompatibility

Abstract: A B S T R A C TMechanical properties and in vitro biocompatibility of graphene/hydroxyapatite (HA) composite synthesized using spark plasma sintering (SPS) are reported in this study. Raman spectroscopy corroborated that graphene nanosheets (GNSs) survived the harsh processing conditions of the selected SPS processing parameters. A 1.0 wt.% GNS/HA composite exhibits $80% improvement in fracture toughness as compared to pure HA. GNS pull-out, grain bridging by GNS, crack bridging and crack deflection are the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
185
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 240 publications
(194 citation statements)
references
References 30 publications
6
185
0
3
Order By: Relevance
“…HA ceramic containing 1.0 weight (wt) % graphene exhibited ∼80% improvement in fracture toughness. 24 The main toughening mechanisms which originated from the presence of the graphene are contributed to grain bridging, crack bridging, and crack deflection.…”
mentioning
confidence: 99%
“…HA ceramic containing 1.0 weight (wt) % graphene exhibited ∼80% improvement in fracture toughness. 24 The main toughening mechanisms which originated from the presence of the graphene are contributed to grain bridging, crack bridging, and crack deflection.…”
mentioning
confidence: 99%
“…The results are a solid indication that Gr acts effectively as a nano-reinforcement filler, by providing frictional pull out, crack deflection, and crack bridging as the major toughening mechanisms to resist crack propagation [1]. The high specific surface area of the graphene nanosheets creates an increased contact area with the hydroxyapatite matrix, significantly enhancing the bonding strength between the graphene and hydroxyapatite grains.…”
Section: Morphological Characterizationmentioning
confidence: 86%
“…Recent studies employing graphene as an ideal reinforcement material for hydroxyapatite have demonstrated the significant toughness and strength of the composites, which retain their biocompatibility without any offsetting bioactivity [1,[14][15][16]. It is worth mentioning that, for biomedical purposes, graphene has been used along with chitosan in composites that reportedly show a 200 times increase in elasticity modulus compared to undoped chitosan [17].…”
Section: Antibacterial Activitymentioning
confidence: 99%
See 2 more Smart Citations